THE MAIN ISSUES OF IQA IN THE HIGHER EDUCATION SYSTEM IN UZBEKISTAN AND ITS POSSIBLE SOLUTIONS - Juraev , Zafar; Kurbonov , Muzaffar (Educational Research in Universal Sciences, 2023)
In the dynamic landscape of education, quality assurance stands as the bedrock upon which a nation’s future is built. In Uzbekistan, a country with a rich history and a vision for progress, the concept of Internal Quality Assurance (IQA) has gained increasing significance in recent years. As the nation strives to provide its citizens with a world-class education, it is crucial to address the main issues that currently plague IQA within its educational institutions.